A preliminary global geologic map of Vesta based on high-altitude mapping orbit data - Yingst, R. Aileen; Mest, S.; Garry, W. Brent; Williams, David A; Berman, D.; Jaumann, R.; Pieters, C.M.; Ammannito, E.; Buczkowski, D.L.; De Sanctis, M. C.; Frigeri, A.; Le Corre, L.; et al. (2012)
Previous maps of the asteroid Vesta were derived from albedo and elevation (Hubble Space Telescope, 38-52 km/pixel), and color data and Earthbased spectroscopy were utilized to generate mineralogic and lithologic maps [1-6]. The Dawn spacecraft has acquired images of Vesta at resolutions up to 500x higher, allowing us to advance from simple identification of the largest spatial and spectral features to complex geologic mapping of morphologic units and features, including stratigraphic and structural relationships. We here report on a 1:500,000-scale preliminary global map of Vesta, based on data from the High- Altitude Mapping Orbit (HAMO). This map is part of an iterative mapping effort; the geologic map is refined with each improvement in resolution [e.g., 7]. Geologic Setting: Vesta is an ellipsoidal asteroid with an equatorial radius of ~283 km. It has been identified as the parent body for the Vestoids and the HED (howardite-eucrite-diogenite) family of meteorites. By dating HEDs, Vesta has been determined to be ~4.56 by old [8-10]. Previous data revealed that it has a surface composed of pyroxene-bearing minerals [e.g. 1- 3]. Vesta has a heavily-cratered surface, with large basins evident in numerous locations. The south pole in particular is dominated by an impact basin so large it was identified before Dawn’s arrival; this basin has been named Rheasilvia. The surface is also characterized by a system of deep, globe-girdling equatorial troughs and ridges, as well as an older system to the north. Troughs and ridges are also evident cutting across, and spiraling arcuately from, the Rheasilvia central mound [11].